Isolation and monoculture of functional primary astrocytes from the adult mouse spinal cord - Peterson, Ingrid L.; Thompson, Austin D.; Scholpa, Natalie E.; Largent-Milnes, Tally; Schnellmann, Rick G. (Frontiers in Neuroscience, 2024)
Astrocytes are a widely heterogenic cell population that play major roles in central nervous system (CNS) homeostasis and neurotransmission, as well as in various neuropathologies, including spinal cord injury (SCI), traumatic brain injury, and neurodegenerative diseases, such as amyotrophic lateral sclerosis. Spinal cord astrocytes have distinct differences from those in the brain and accurate modeling of disease states is necessary for understanding disease progression and developing therapeutic interventions. Several limitations to modeling spinal cord astrocytes in vitro exist, including lack of commercially available adult-derived cells, lack of purchasable astrocytes with different genotypes, as well as time-consuming and costly in-house primary cell isolations that often result in low yield due to small tissue volume. To address these issues, we developed an efficient adult mouse spinal cord astrocyte isolation method that utilizes enzymatic digestion, debris filtration, and multiple ACSA-2 magnetic microbead purification cycles to achieve an astrocyte monoculture purity of ≅93–98%, based on all markers assessed. Importantly, the isolated cells contain active mitochondria and express key astrocyte markers including ACSA-1, ACSA-2, EAAT2, and GFAP. Furthermore, this isolation method can be applied to the spinal cord of male and female mice, mice subjected to SCI, and genetically modified mice. We present a primary adult mouse spinal cord astrocyte isolation protocol focused on purity, viability, and length of isolation that can be applied to a multitude of models and aid in targeted research on spinal-cord related CNS processes and pathologies.